2011
DOI: 10.1002/adem.201100029
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Manufacturing Route for Fabrication of Topologically‐Ordered Porous Magnesium Scaffolds

Abstract: The use of porous metal foams as biomaterial scaffolds has been widely adopted; however, many of these porous structures are manufactured with pore architectures that are inherently random. This makes structural optimization for a specific purpose challenging. Scaffolds containing ordered pore architectures can be fabricated to meet design criteria, such as porosity, stiffness, and volume fraction. Mg and its alloys offer potential as a new class of degradable metallic orthopedic biomaterials. In comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 35 publications
2
51
0
Order By: Relevance
“…[80] Singh and co-workers presented a novel method for production of titanium foams for biomedical implants. The multi-step method involved the printing of an SFF mold, NaCl infiltration, and liquid Mg casting techniques.…”
Section: Irregular Structuresmentioning
confidence: 99%
“…[80] Singh and co-workers presented a novel method for production of titanium foams for biomedical implants. The multi-step method involved the printing of an SFF mold, NaCl infiltration, and liquid Mg casting techniques.…”
Section: Irregular Structuresmentioning
confidence: 99%
“…When this is compared with the temperature of molten magnesium, there is a small probability of this reaction. A TGA-DTA research [20] performed on a mixture of Mg þ CaCO 3 , preheated above the melting point of Mg, proved that the foaming gas is CO produced in an exothermic reaction (8):…”
Section: Melt Foaming Methodsmentioning
confidence: 99%
“…[36] Moreover, it was found that Mg alloys passivation process will be easier in the presence of F À ions. [37] Another research showed that using a supersaturated Na 2 SO 4 solution [8] could handle corrosion problems. Furthermore, resulting from such leaching only negligible concentrations of Cl À (< 0.3%) were detected.…”
Section: Preform Infiltrationmentioning
confidence: 99%
See 2 more Smart Citations